The Impact of Online Learning on Mathematics Subjects in Elementary Schools - Novi Handra (JENIUS (Journal of Education Policy and Elementary Education Issues), 2022)
Mathematics is one material that looks quite draining. Learning Mathematics requires special objects and explanations from the teacher. The coronavirus outbreak has allowed all learning to be online, including Mathematics. This study describes the learning process during the coronavirus pandemic and the impact of online learning in mathematics learning. This research method is a qualitative method using interviews and literature research. The results of this study are that the Mathematics learning process is carried out online at school, and some still require parents to bring their children's homework to school. In this pandemic, teachers, students and parents feel various influences during online learning, some of which are positive or negative